Risk related behavior of the youth, using natural radiation and solariums with diagnosed nevi among residents of villages - Lewandowska, Anna; Ożóg, Renata; Laskowska, Barbara; Lewandowski, Tomasz (Journal of Education, Health and Sport, 2017)
Objective: Solar radiation is the most frequent environmental factor influencing the skin, where responsibility for harmful properties are of the ultraviolet radiation. Excessive exposure to ultraviolet radiation significantly increases the risk of occurrence pigmented or non-pigmented skin cancers – melanoma or squamous-cell cancer. Cancerous effect is observed through artificial tanning. International agency for Research on Cancer in 2009 classified the radiation emitted by solar lams as carcinogen factor for skin cancer, equally with other carcinogens, such as arsenic compounds, coal tar and soot The aim of the work is to analyze risk behavior of the youth using natural radiation and tanning beds with diagnosed nevi. Material and methods: The research was carried among 500 people residing on the territory of Podkarpackie Voivodship. The age of test subject ranged between 18 to 25 years, the test group consisted of 93% women and 7% men. To acquire the research material for the work, physical examination was conducted to assess the occurrence of skin lesions, dermatoscopy to assess nevi and skin changes, standardized questionnaire form including questions to spontaneous and supported answers. Results: Physical examination proved the occurrence of nevi with 68% of test subjects, where after dermatoscopy 25% of changes indicated worrying cancerous features and further dermatological examinations were recommended (page 1-7). All subjects (100%) with pigment changes have sunbathed or used tanning bed at least once in a lifetime, and over a half (68%) were sunburned through UV radiation. Conclusions: Majority of interviewees believe that natural tanning was the cause of more frequent sunburns than solarium tanning. Majority of the youth is systematically using solarium tanning without the consent of the public. People who tan naturally and concurrently appropriately select and apply sunscreen to their skin tone, are less sunburned.